2016
DOI: 10.1111/tra.12384
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Cell‐Based Analysis of Localization of Predicted Drosophila Peroxisomal Proteins

Abstract: Peroxisomes are membrane-bound organelles found in almost all This will facilitate use of Drosophila as a genetically tractable, multicellular model system for studying key aspects of human peroxisome disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 61 publications
1
55
0
Order By: Relevance
“…PEX5 and PEX7 homologues are found across the eukaryota, including kinetoplastids, yeasts, plants and mammals (Kanzawa et al, 2012;Kragler et al, Mutation of Drosophila Pex genes is linked to a range of phenotypes, including lethality (Pex1, Pex3, Pex19) and male sterility (Pex16) (Beard and Holtzman, 1987;Bulow et al, 2018;Chen et al, 2010;Faust et al, 2014;Mast et al, 2011;Nakayama et al, 2011). In Drosophila S2 cells, knock down of Pex5 transcript reduces targeting of PTS1containing proteins to peroxisomes function, while depletion or overexpression of Pex7 transcript led to smaller or larger peroxisomes, respectively, than normal (Baron et al, 2016). However, the actual function of Drosophila Pex7 remains unclear, as no bona fide peroxisomal PTS2-containing protein has been identified in Drosophila; fly homologues of peroxisomal proteins trafficked by the PTS2/PEX7 import pathway, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…PEX5 and PEX7 homologues are found across the eukaryota, including kinetoplastids, yeasts, plants and mammals (Kanzawa et al, 2012;Kragler et al, Mutation of Drosophila Pex genes is linked to a range of phenotypes, including lethality (Pex1, Pex3, Pex19) and male sterility (Pex16) (Beard and Holtzman, 1987;Bulow et al, 2018;Chen et al, 2010;Faust et al, 2014;Mast et al, 2011;Nakayama et al, 2011). In Drosophila S2 cells, knock down of Pex5 transcript reduces targeting of PTS1containing proteins to peroxisomes function, while depletion or overexpression of Pex7 transcript led to smaller or larger peroxisomes, respectively, than normal (Baron et al, 2016). However, the actual function of Drosophila Pex7 remains unclear, as no bona fide peroxisomal PTS2-containing protein has been identified in Drosophila; fly homologues of peroxisomal proteins trafficked by the PTS2/PEX7 import pathway, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the requirement for peroxisomemediated lipid synthesis in cells of the central nervous system. Baron et al, 2016). Together, these data suggest that D. melanogaster Pex7 function is required for normal development of a specific subset of cells, likely of neuronal lineage.…”
mentioning
confidence: 80%
“…The D. melanogaster genome encodes a putative Pex7 homolog only somewhat characterized. To date, different patterns of co-localization of Pex7/peroxisome have been reported, from 0% to 50% co-localized depending on the reporters used (Faust et al, 2012;Baron et al, 2016). There is a requirement for Pex7 in D. melanogaster lipid processing, as homozygous Pex7 mutant larvae have higher levels of circulating free fatty acids and are larger than their wild-type counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, genetic screens for biochemical phenotypes have identified genes implicated in peroxisome-biogenesis, pexophagy, and peroxisomal biochemistry (SUBRAMANI 1998;KAO et al 2018). More recently, microscopy-based screens have uncovered genes implicated in peroxisome morphology (BARON et al 2016;YOFE et al 2017). These studies have shown that the pathways that regulate peroxisome dynamics (i.e.…”
Section: Introductionmentioning
confidence: 99%